Luminescence and energy transfer of Eu2+/Tb3+/Eu3+ in LiBaBO3 phosphors with tunable-color emission1. Issue 35 (21st September 2015) - Xu, Shuchao; Li, Panlai; Wang, Zhijun; Li, Ting; Bai, Qiongyu; Sun, Jiang; Yang, Zhiping
<x xml:space="preserve">Abstract</x> A series of LiBaBO3:RE (RE = Eu2+/Tb3+/Eu3+) phosphors have been synthesized using the high-temperature solid-state reaction method.